Ketorolac eye drops reduce inflammation and delay re-epithelization in response to corneal alkali burn in rabbits, without affecting iNOS or MMP-9 - Lima, Tiago Barbalho [UNESP]; Ribeiro, Alexandre Pinto; Conceição, Luciano Fernandes da [UNESP]; Bandarra, Marcio [UNESP]; Manrique, Wilson Gomez [UNESP]; Laus, José Luiz [UNESP] (Consel Brasil Oftalmologia, 2015)
Purposes: To assess the effects of 0.5% ketorolac tromethamine without preservatives on the expression of iNOS and MMP-9 in alkali burn ulcers.Methods: Twelve eyes of 120-day-old male rabbits were treated (TG) every 6 h with 0.5% ketorolac tromethamine and 12 other eyes were treated with saline solution (CG), immediately after the occurrence of ulcers by 1 M sodium hydroxide (NaOH). Re-epithelialization was monitored using fluorescein every 6 h. After 24 h, six corneas (n=6) of each group were collected (M1). The others (n=6) were collected after reepithelialization (M2). At both moments, the inflammatory infiltrate and the conditions of the newly formed epithelium were histologically analyzed. iNOS and MMP-9 were evaluated by immunohistochemistry.Results: Mean epithelialization time in TG was 55 +/- 0.84 h. In CG, it was 44 +/- 1.06 h (p=0.001). At M1, corneas of TG had lower inflammatory exudation compared with (p<0.001). At M2, TG revealed discrete inflammatory exudation (p>0.05) and lower numbers of epithelial layers compared with CG. The mean iNOS in stromal cells did not differ in TG over both moments compared with CG (p>0.05) At M2, the central corneal region expressed more iNOS in both groups compared with the peripheral region. No significant differences were observed in iNOS scores of epithelial immunostaining between the groups and across M1 and M2 (p=0.69). Epithelial immunostaining scores for MMP-9 did not differ in TG compared with CG (p=0.69). The average immunostaining score of MMP-9 in stromal cells showed no differences between groups or moments. There was no correlation between immunostaining of iNOS and MMP-9 or between the amount of inflammatory cells and immunostaining of iNOS.Conclusions: Use of 0.5% keratolac tromethamine reduced inflammation and delayed reepithelialization in a cornea alkali burn model without impacting the expression of iNOS or MMP-9.

Objetivos: Avaliarem-se os efeitos do cetorolaco de trometamina 0,5%, sem conservante, sobre a expressão da iNOS e da MMP-9, em córneas com úlceras químicas. Métodos: Doze olhos de coelhos machos, 120 dias de idade, foram tratados (GT ), a cada 6 horas, com o cetorolaco de trometamina 0,5% e outros 12 com solução salina (GC), imediatamente à ocorrência de úlceras por hidróxido de sódio (NaOH) 1 mol/L. A reepitelização foi monitorada por fluresceína a cada seis horas. Decorridas 24 horas, seis córneas (n=6) de cada grupo foram colhidas (primeiro momento). As demais (n=6) o foram após a sua reepitelização (segundo momento). Em ambos os momentos, avaliaram-se o infiltrado inflamatório e as condições do epitélio neoformado (HE). Por imuno-histoquímica, avaliou-se a imunomarcação de iNOS e de MMP-9. Resultados: A média do tempo de epitelização no GT foi de 55 ± 0,84 horas. No GC, ela foi de 44 ± 1,06 horas (p=0,001). Às 24 horas, as córneas do GT apresentaram menor exsudação inflamatória (p<0,01). No segundo momento, o GT mostrou discreta exsudação inflamatória (p>0,05) e menor número de camadas epiteliais comparativamente ao GC. A média de imunomarcação de iNOS em células do estroma não diferiu do GT, em ambos os momentos (p>0,05). No segundo momento, a região central da córnea expressou mais iNOS, comparativamente à periférica, em ambos os grupos. Não se observaram diferenças significativas nos escores de imunomarcação epitelial de iNOS entre os grupos e os momentos (p=0,69). Os escores de imunomarcação epitelial para MMP-9 não diferiram entre os grupos (p=0,69). A média de imunomarcação da MMP-9 em células do estroma não exibiram diferenças entre os grupos e momentos da avaliação (p=0,32). Não houve correlação entre a imunomarcação de iNOS e de MMP-9, assim como quanto ao quantitativo de células inflamatórias e à imunomarcação de iNOS. Conclusões: Cetorolaco 0,5% reduziu a inflamação e atrasou a epitelização na queimadura corneal por álcali sem alterar a expressão de iNOS ou MMP-9
Colírio de cetorolaco reduz inflamação e atrasa a epitelização em resposta a queimadura por álcali em coelhos, sem afetar iNOS ou MMP-9
Keywords: Corneal ulcer/chemically induced; Ketrolac tromethamine/administration; iNOS; MMP-9; Úlcera da córnea/induzida quimicamente; Cetorolaco de trometamina/ administração; iNOS; MMP-9